2000
DOI: 10.1177/002215540004800910
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Immunogold Localization of Protein Phosphatase 2B (Calcineurin) inParameciumCells

Abstract: S U M M A R YFor immunogold EM labeling analysis, we fixed Paramecium cells in 4% formaldehyde and 0.125% glutaraldehyde, followed by low-temperature embedding in unicryl and UV polymerization. We first quantified some obvious but thus far neglected side effects of section staining on immunogold labeling, using mono-or polyclonal antibodies (Abs) against defined secretory and cell surface components, followed by F(ab) 2 -or protein A-gold conjugates. Use of alkaline lead staining resulted in considerable rearr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 73 publications
3
21
0
Order By: Relevance
“…This report conclusively demonstrates the existence of both CaNA and CaNB gene families in Paramecium, as suggested by previous enzymatic (45,46), and antibody binding studies (62,63). Moreover, there is considerable evolutionary conservation of these families with both subunits recognized by antibodies generated to their mammalian counterparts.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This report conclusively demonstrates the existence of both CaNA and CaNB gene families in Paramecium, as suggested by previous enzymatic (45,46), and antibody binding studies (62,63). Moreover, there is considerable evolutionary conservation of these families with both subunits recognized by antibodies generated to their mammalian counterparts.…”
Section: Discussionsupporting
confidence: 85%
“…This fits the generally broad spectrum of CaN substrates that may be phosphorylated by widely different kinases (86) and the multifunctional activity of CaN (47,80,86). All of these molecules, including the kinases, together with CaN and pp63, colocalize to the narrow space between the cell membrane and cortical calcium stores, as well as around the docking sites of trichocysts (42,62). Few details are known about possible kinases or phosphatases involved in regulating swimming behavior in Paramecium.…”
Section: Discussionmentioning
confidence: 55%
“…Meanwhile we also localized CaN in Paramecium by semiquantitative EM-gold labeling. The label was concentrated on the complex formed by a plasma membrane and alveolar sacs on the infraciliary lattice, rims of heterochromatic areas of the macronucleus and parasomal sacs (Momayezi et al, 2000). This largely reflects the distribution of the biochemically defined substrate molecules reported in the literature.…”
Section: Note Added In Proofmentioning
confidence: 54%
“…In the Paramecium cell cortex, any Ca 2 +-release channels would have to be located on the outer part of alveolar sacs, because the part facing the cell center is densely studded with Ca 2 +-pump molecules [56]. In agreement with this postulate, the subplasmalemmal space, including that delineated by alveolar sacs and trichocysts, is the site where pp63/pf [36], as well as the relevant protein phosphatase PP2B/CaN [42] and protein kinases CK-2 and PKG [57,58] are heavily enriched according to immuno-EM studies (see Fig. 1 and below).…”
Section: Introductionmentioning
confidence: 86%
“…The respective EMBL accession numbers are AF014922 (Hinrichsen lab) and AJ567906 (this lab) for SU-A, as well as AJ554047 and AJ554048 for SU-B, respectively. Immunostimulation of e ocyto is localisation studies at the EM level showed that both SUs occur in domains predetermined for exocytosis performance and in adjacent areas, i.e., in part in association with alveolar sacs [42]; Fig. 1.…”
Section: Introductionmentioning
confidence: 96%